A robust RGB channel based image steganography technique using a secret key - Bairagi, Anupam Kumar; Mondal, Saikat; Debnath, Rameswar (16th Int'l Conf. Computer and Information Technology, 2014)
The paper proposes a RGB channel based steganographic technique for images imparting better information security. This technique inserts the information into deeper layers of the selected RGB channel and the position is determined depending on the status of channel and value of the secret key. Pixels of the cover image are selected depending on the environment of the channels and hidden information. The ambiguity of pixel, channel and position selection process increases robustness of the steganographic system. The technique is also less vulnerable to unintentional attacks like image manipulation as data hides in the deeper layer of the pixels. The system uses the RGB channels of the stego-image and the secret key to extract the hidden information. The use of secret key gives another way to secure the information from malicious user. The experiment shows that on average 77.00% pixels of the cover image are used for hiding secret information and produces high PSNR value which indicates the capacity and imperceptibility of the technique respectively.